Heteropagus conjoined twins: Five cases - Mahamat-nour Abakar Djibrine; Olivier Ngaringuem; Youssouf Djidita Hagré; Adami Adam; Khadidja Attimer; Ouchemi Choua (Elsevier, 2022)
Aim: report cases of heteropagus conjoined twins on and results of their management. Method: Prospective descriptive study of all heteropagus cases operated at the pediatric surgery department of the mother and child teaching hospital over five years. Results: We collated 5 cases of heteropagus conjoined twins with a frequency of 1.89/1 million births. The mean age of patients at surgery was 5 months, with extremes of 13 days and two years. The sex ratio was 1/4. There were two omphalopagus cases, one pygopagus case, one unusual localization of the parasitic on the face and one localization on the back. All patients were delivered vaginally and no antenatal diagnosis was made. The removal of the parasitic was complete in all cases. The mean operating time was 73 minutes. We noted surgical wound suppuration in 60% of cases. Conclusion: We collated 5 cases of heteropagus conjoined twins in 5 years, with complete separation carried out in all cases. An imaging workup is crucial to guide surgery. Our challenge is to stimulate investigations to determine the causes of the high frequency of heteropagus conjoined twins in our community.